Serum biomarker-based risk model construction for primary Sjögren’s syndrome with interstitial lung disease - Liu, Xiaoli; Zhang, Xia; Shi, Juan; Li, Shiqing; Zhang, Xiuzhi; Wang, Huiling (Frontiers in Molecular Biosciences, 2024)
Background: Cytokine network disturbances in primary Sjögren's syndrome (pSS) have been reported in many studies. However, their functions in patients with primary Sjögren's syndrome and interstitial lung disease (pSS-ILD) have been controversial. In this study, we aim to investigate the associations of immunological characteristics and cytokine profiles with pSS-ILD pathogenesis and explore their predictive values for pSS progression.Methods: A total of 256 patients initially diagnosed with pSS at Henan Provincial People's Hospital were collected. After excluding the patients previously diagnosed with various serious acute and chronic respiratory system diseases and the cases coexisted with other connective tissue diseases or congenital heart diseases, 94 pSS patients were included for further analysis, including 40 patients with ILD (pSS-ILD) and 54 patients without ILD (pSS-N-ILD). For comparison, 41 age-and sex-matched healthy individuals were included as normal controls. Their clinical symptoms and serological data including cyclic citrullinated peptide (CCP) antibody (anti-CCP), antinuclear antibody (ANA), anti-Ro52, anti-SSA, anti-SSB, C-reactive protein, IgG, IgM, IgA, C3, C4, and 10 cytokines and chemokines were obtained. Wilcoxon test, Chi square test, Spearman correlation analysis and logistics regression analysis were performed.Results: Higher positive rates of anti-SSB, and higher incidence of dry cough, dyspnea and arthrosis symptoms were shown in pSS-ILD patients than the pSS-N-ILD cases.Anti-CCP antibody and cytokines (IL-1β, TNFα, IL-6, IL-5, IL-12p70 and IL-17) were higher while C3 was lower in pSS-ILD patients than those in pSS-N-ILD cases.Significant negative correlations of IgG with C3 and C4 while positive correlations of IL-12p70 and IL-17 with IL-6 were only shown in pSS-ILD patients. Anti-CCP antibody was positively correlated with IL-5 in pSS-ILD patients, but not in pSS-N-ILD cases. Multivariable logistics regression analysis revealed the combination of anti-CCP, IL-17, IL-12p70 and IL-5 was effective in predicting the status of pSS-ILD in the pSS cases.There were significant differences of serum marker levels between pSS-ILD and pSS-N-ILD cases. The combination of anti-CCP, IL-17, IL-12p70 and IL-5 might be a potential risk predictor for pSS-ILD occurrence. The cytokines might be involved in the development and progression of pSS-ILD. These results would provide new therapeutic targets for pSS-ILD treatment.